Minor Characters Have Their Day. - Rosen, Jeremy (Columbia University Press, 2016)
How do genres develop? In what ways do they reflect changing political and cultural trends? What do they tell us about the motivations and desires of publishers and readers? Combining close readings and formal analysis with a sociology of literary institutions and markets, Minor Characters Have Their Day offers a compelling new approach to genre study and contemporary fiction based on its analysis of the booming genre of novels that transform minor characters from canonical literary texts into the protagonists of new works. Focusing on a crucial yet frequently unacknowledged genre, Jeremy Rose.